Are Clinical Pilates Exercises an Effective Treatment for Scoliosis? A Randomized Clinical Trial - Başaran Özden, Ceren; Kuru Çolak, Tuğba (Journal of Health and Allied Sciences NU, 2022)
Objectives The aim of the study was to investigate the effectiveness of clinical Pilates exercises in patients with idiopathic scoliosis.Materials and Methods The study included patients aged 15 to 30 years with adolescent idiopathic scoliosis. Patients were randomly separated into the following two groups: the clinical Pilates exercise group (n = 16) and the control group (n = 18). The clinical Pilates exercise group received 16 sessions of exercise. Angle of trunk rotation (scoliometer), sagittal plane alignment of the spine (inclinometer), posture (PostureScreen Mobile program), quality of life (Scoliosis Research Society-23), pain (Numerical Pain scale), and cosmetic deformity perceptions (spinal appearance questionnaire) were assessed twice.Statistical Analysis Data obtained in the study were analyzed statistically using IBM, SPSS v. 22 software. The Shapiro–Wilks test was used to assess the conformity of data to normal distribution. In the group comparisons of angle of rotation, kyphosis and lordosis angle, and anterior shift values obtained at baseline and in the 8th week, the independent sample t-test were applied to variables with normal distribution, and the Mann–Whitney U test to variables not showing normal distribution.Results The change in the pain score from baseline to 8 weeks was determined to be significantly superior in the Pilates group (p < 0.001). A statistically significant difference was determined between the groups in respect of the amount of change in the side shift and tilt measurements in the posture evaluation, with superior improvement seen in the Pilates exercise group(p < 0.005).Conclusions The results of this study showed that Pilates exercises did not have a significant effect on deformity, quality of life, and perception of deformity in scoliosis, but significantly reduced back and low back pain and contributed to improvements in posture.
Keywords: adolescent; exercise; scoliosis; rehabilitation